Démons iraniens: actes du colloque international organisé à l'Université de Liège les 5 et 6 février 2009 à l'occasion des 65 ans de Jean Kellens - Swennen, Philippe; Kellens, Jean (Collection religions, 2015)
Iranian demons belong to the generic category of "daēuua-" ("dev" in Pahlavi). And yet the word is derived from the same Sanskrit word ("devā-") that originally meant "god," as the Latin "deus" attests. How did this change in meaning come about? Did Zoroaster, famous as the founder of the Mazdean doctrine, play a role in the redefinition of the semantic content of the word "daēuua-"? Does its evolution reflect a distinctive trait of the religion of the archaic Iranian world? How does the concept of demon change over the long history of ancient Iranian religion? What role did demons play in Mazdean religious ceremonies? The contributions in this volume respond to these and related questions